MMSE 검출기에서 다중경로 이득 개선에 관한 연구 - 유동관(Dong-Kwan Yoo) (韓國컴퓨터情報學會論文誌, 2005)
In this paper, an improved detection method is Proposed by supplementing multi-path gain for a MMSE detecter. This method is Proposed to complement the shortcomings of the conventional detection method which is used for multiuser detection in STBC CDMA system. We analyzed the improved method in bit error Probability viewpoint and compared the result with that of the conventional method In this result, we showed that the improved method obtains better performance of bit error probability than the conventional method when parameters such as delay, number of user and SNR are increased. 본 논문에서는 다중 사용자 환경의 STBC CDMA 시스템에서 기존의 USE 검출방식이 여러 경로의 수신신호 중에서 가장 전력이 강한 신호만을 사용하므로 상대적으로 검출 능력이 떨어지는 단점이 있어 이를 보완한 검출방식을 제안한다. 제안한 방식은 각각의 다중경로의 수신신호에 여러 가지 방법으로 혼합된 이득을 적용한 뒤 이들을 결합하여 성능을 개선시킨 방식이다. 개선된 검출방식의 성능분석은 비트오율 확률 분포 관점에서 이루어졌으며 이것을 기존 USE방식과 비교하였다. 그 결과 다중경로 이득을 여러 가지 방법으로 혼합하여 적용시킨 개선된 검출방식이 기존의 방식보다 채널의 지연 값, 사용자 수, 신호 대 잡음비에 대한 비트 오율 확률분포의 성능이 더 향상됨을 알 수 있었다.